Experimental and numerical study on the CO formation mechanism in methane MILD combustion without preheated air. (15th March 2017) - Liu, Yang; Cheng, Jia; Zou, Chun; Cai, Lei; He, Yizhuo; Zheng, Chuguang
Highlights: Local high O2 concentration was the reason for high CO concentration zone appeared. R166, R167, R168 plays a significant role in CO formation during MILD combustion. In the central zone, the main CO2 formation path was CH4 → CH3 → CH3 O → CH2 O → HCO → CO → CO2 . R99 dominated in the CO consumption in the recirculation zone. Abstract: Moderate or intense low-oxygen dilution (MILD) combustion has increasingly attracted the attention of scholars because of its high efficiency and low-pollutant emission, particularly its emission of CO and NOX . MILD combustion without preheated air was achieved in this study. Numerical results obtained by a computational fluid dynamics model with GRI-Mech 3.0 conform well to those from the experiments. Three zones, namely, central zone, high CO concentration zone, and recirculation zone, were found in the furnace. The CO formation mechanisms were analyzed in the three zones by examining the rate of production. Analysis results showed that the reason for the appearance of high CO concentration zone was local high O2 concentration. High O2 concentration enhanced the reaction O + CH3 ⇔ H + CH2 O, which resulted in an amount of CH2 O. High O2 concentration also enhanced the radical pool reaction H + O2 ⇔ OH + O, which produced an amount of O radicals. Thus, reaction O + CH4 ⇔ OH + CH3 was enhanced, and it had the largest production rate of OH and CH3 . The OH radical led to an amount of HCO through the reaction OH + CH2 O ⇔ HCO + H2 O, and CH3 radical favored the production of CH2 O. An amount of HCO was converted to CO by HCO + O2 ⇔ HO2 + CO, HCO + H2 O ⇔ H + CO + H2 O, and HCO + M ⇔ H + CO + M. The main CO formation path was CH4 → CH3 → CH3 O → CH2 O → HCO → CO in the central zone. The majority of CO in the recirculation zone came from the central or high CO concentration zones by convection or diffusion, and it was consumed by OH + CO ⇔ H + CO2 .